Artificial intelligence in public administration: opportunities, challenges, and ethical considerations - Malawani, Ajree Ducol (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study explores the integration of artificial intelligence (AI) into public administration, focusing on its potential to enhance governance, service delivery, and decision-making. AI technologies such as machine learning, big data analytics, and natural language processing offer opportunities to improve efficiency and automate processes. However, challenges such as algorithmic bias, data privacy risks, and bureaucratic resistance hinder implementation. This paper reviews existing literature to identify key trends, challenges, and implications for policymakers. Using a literature review, this study synthesises research from Scopus and ScienceDirect, prioritising studies from the past ten years. A thematic analysis categorises findings into AI applications, social media, and big data in governance, as well as ethical concerns and adoption challenges. The review highlights AI’s transformative potential while emphasising the need for strong regulatory frameworks, ethical guidelines, and capacity-building. Consequently, social media possesses abundant information that can be leveraged in the development of artificial intelligence. Hence, AI has the potential to modernise public administration, but its success depends on transparency, accountability, and inclusivity.